Penerapan Prinsip Prinsip Good Governance dalam Pelayanan Administrasi Kependudukan di Dinas Kependudukan Dan Pencatatan Sipil Kota Bekasi - Latifah Zahroh; Lina Aryani; Evi Priyanti (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
Studies on good governance in public services have been widely conducted; however, most have focused on village financial management, and public information access and infrastructure development. Research specifically examining the implementation of good governance principles in population administration services, particularly at the Population and Civil Registration Office (Disdukcapil) of Bekasi City, remains limited. This study aims to analyze the application of good governance principles in population administration services at the Population and Civil Registration Office of Bekasi City. The method used is qualitative with a case study approach. Data were collected through in-depth interviews, observations, documentation and audio-visual materials, then analyzed using pattern matching techniques. The results show that accountability is implemented through standard operating procedures (SOPs) and routine evaluations; transparency is realized through the utilization of various information media both online and offline, although digital literacy among the community remains a challenge; openness is reflected in the provision of multiple complaint channels, but their utilization is not yet optimal; and legal regulations are enforced clearly, along with non-discriminatory services for vulnerable groups. These findings indicate that the implementation of good governance principles at Disdukcapil Bekasi City has been fairly consistent; however, it still requires strengthened service socialization, optimization of digital complaint mechanisms, and improved service accessibility to enhance accountable, transparent, and inclusive population administration services.